Evaluating delamination at entry of drilled carbon fiber reinforced polymer (CFRP) composite with diamond coated ball nose drills - Konneh, Mohamed; Al Hazza, Muataz Hazza Faizi; Sidek, Atiah Abdullah (Trans Tech Publications, Switzerland, 2015)
This paper presents the investigation of the influence of machining parameters on delamination at entry of drilled holes after drilling into CFRP composite using 4 mm-diameter 2- fluted carbide drills coated diamond. The delamination at tool entry was analyzed in terms of delamination factor on the basis of analysis of variance (ANOVA) of Central Composite Design (CCD) of experiments. It is found that spindle speed is the most influential factor for the drilling of CFRP within the range of cutting parameters examined. The lowest delamination factor (1.006) was generated at rotational speed, 4400 rpm and feed rate, 270 mm/min; and the highest delamination factor (1.123) generated at rotational speed, 537 rpm and feed rate, 180 mm/min. A mathematical model has been predicted for the delamination at tool entry. The relationship between the machining variables and output variables is also established